Production technology of Nabataean painted pottery compared with that of Roman terra sigillata - Tite, M.; Herringer, S. N.; Shortland, Andrew J.; Matin, M.; Pradell, T.; Alcock, S. E. (Elsevier, 2016)
The Nabataeans, who founded the city of Petra (southern Jordan) in the late first millennium BCE, are noted for the production of a distinctive very fine pottery with painted decoration and a wall thickness sometimes as little as 1.5 mm; this pottery appears largely locally made and not widely circulated. Using a combination of OM, SEM with attached EDS, surface XRF, and XRD, it is shown that the Nabataean fine pottery bodies were produced using semi-calcareous clays which were fired to temperatures of about 950 °C. In contrast, published data indicate that contemporary and in many ways apparently functionally equivalent Roman terra sigillata, which was traded throughout the Roman Empire, was produced using fully-calcareous clays which were fired to temperatures in the range 1000–1100 °C. Furthermore, the high gloss slip applied to Roman terra sigillata is fully vitrified whereas the red-painted decoration applied to the Nabataean pottery is unvitrified. The more robust Roman terra sigillata is therefore better suited as tableware for serving and consuming food than would be the case for Nabataean fine pottery, and would be a more successful export material.
Keywords: Archaeology; Pottery; Terra sigillata; Slips; Nabataean; Roman; Calcareous clays; Firing temperatures